Analisis Agenda Setting Pemberitaan MotoGP Mandalika Pada RRI Mataram - Hayatun Sofian; Yulanda Trisula SY; Sandi Justitia Putra; Lalu Ahmad Rahmat; I Made Putra Suryantara (MUKASI: Jurnal Ilmu Komunikasi, 2022)
This research has an important urgency because the public will tend to pay attention to the things that are the priority of mass media coverage. The media setting agenda can relate the possible effects of influencing public opinion or opinion so that it does not only pay attention to priority news but also learns how important the way the mass media prioritizes news topics is. Formulate the problem in this study is "How is the agenda setting of the Mandalika MotoGP News RRI Mataram?" The research approach used by the researcher is qualitative. Determination of the main issues and other supporting news through a long process that is discussed in the agenda setting meeting. The negative and positive sides of the MotoGP event will be published in news bulletins so that reporters will be assigned to the field to find sources. The selection of sources is adjusted to the topic of the news/coverage. Resource persons are selected based on the competence of the position, the suitability of the substance of the problem and the ability to act as a decision maker. After the news topics are determined, the next job is to do the coverage. Coverage is done to dig up data and facts, to be processed into news. This is where the reporter plays a very important role. The reporter's tenacity and tenacity are tested, because coverage is not always easy because sources are often hard to find. Therefore the reporter must make a coverage plan. The coverage plan must include the following: What or who will be the object/subject of the coverage, Where will the coverage be carried out, What information will be obtained (Questions should be prepared in the form of open-ended questions) What is the angle of the news?, Who Will the right sources be found to strengthen the news?.The researcher concludes that Agenda Setting is a forum for discussing the main topic or issue based on considerations such as the issue being discussed by the community How significant the issue is for the community or listeners The issue can also be considered from whether other media carry it Agenda Setting has a very important and strategic role in concocting and framing news, especially about the MotoGP world motorcycle racing event at the Mandalika Circuit, Central Lombok. Even from the agenda setting, synergistic communication was created by reporters, editors and deputy editors who were very harmonious even though there were debates in determining the main issues to be presented in the RRI Mataram news bulletin. RRI Mataram as a Public Broadcasting Institution in MotoGP reporting is independent and neutral so that the information does not favor certain parties but is more in the public interest.